Pengaruh Pembelajaran multiliteracy terhadap Kemampuan academic writing dan Teaching skill pada Semester VIII Program Studi Pendidikan Agama Islam Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Isno, Mohammad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Prospective 21st century primary education teachers who are effective should have a thorough understanding and knowledge of key concepts that drive all content instruction. These key concepts, connected to other core standards, include candidate knowledge and assessment, the nature of the learner, school governance and culture, learning and development theory, the use of critical technology and an understanding of how art influences and interacts. with all other content areas. In addition, prospective teachers should have the necessary information regarding time management, planning for acquisition, dissemination and management of materials and equipment (NCDPI, 2009). The purpose of this study are: 1) Describe the influence of multiliteracy learning on the ability of academic writing in Semester VIII Islamic Religious Education Studies Program Tarbiyah High School Raden Wijaya Mojokerto. 2) Describe the influence of multiliteracy learning on Teaching skill in Semester VIII Islamic Religious Education Studies Program Tarbiyah High School Raden Wijaya Mojokerto. From the analysis can be summarized as follows: 1) From the analysis known that Multiliteracy Learning to the ability of academic writing in semester VIII Islamic Religious Education Studies Program Tarbiyah High School Raden Wijaya Mojokerto with the value obtained Fhitung 15 641 (significance F = 0,000). So Ft> Ftable (14 660> 1.60) or Sig F <5% (0,000 <0.05). This means that learning with multiliteracy learning has an effect on the ability of academic writing in semester VIII Islamic Religious Education Studies Program Tarbiyah High School Raden Wijaya Mojokerto. then the null hypothesis (H0) is rejected and the Hypothesis of work (H1) is accepted. 2) From the results of the analysis shows that multiliteracy learning on Teaching skill in semester VIII Islamic Religious Education Studies Program Tarbiyah High School Raden Wijaya Mojokerto value obtained Fhitung 2,924 (significance F = 0,007). So F arithmetic> F table (2,924> 1.70) or Sig F <5% (0.009 <0.05). This means learning with multiliteracy learning to influence learning achievement in semester VIII Islamic Religious Education Studies Program Tarbiyah High School Raden Wijaya Mojokerto.